Pengaruh Pemberian Beberapa Konsentrasi Bahan Pengawet Chrysal terhadap Kesegaran Bunga Sedap Malam (Polianthes tuberosa) - ERIADI, I KOMANG ALIT; SUKEWIJAYA, I MADE; SUTEDJA, I NYOMAN (Agrotrop : Journal on Agriculture Science; Vol 7 No 1 (2017), 2017)
Effect of several concentrations of preservatives Chrysal the tuberose flower freshness (Polianthes tuberosa). Nowadays, ordering tuberosa cut flower is increasing, but the main problem which is often happen for tuberose flower is the short vase life of tuberose cut flower freshness. One of appropriate strategies that can be used to improve flower freshness is the use of preservatives. The main function of preservatives is as improving for the vase life of cut flower freshness. Chrysal preservatives are a soaking liquid which contains sucrose, dextrose, and citric acid in order to improve vase life of flower. This research is aimed to identify the influence of Chrysal to improve vase life of tuberose flower freshness. This research is conducted in Post-harvest Technology Laboratory of Agriculture Technology Faculty in Udayana University. This research uses complete random sequences (RAK) based on one factor namely Chrysal concentrative. Each action including five repetitions and a trial includes two stems of tuberose cut flower. The outcome shows that Chrysal concentrative influences the significant for four variables namely, percentages of flower blossom, flower freshness, long flower freshness, and the total of absorbed solution. The actions of concentrative Chrysal influence significant for weight loss. The short vase life of flower freshness are haven on using Chrysal concentrative 0 mg (C0) along four days, and the long vase life of flower freshness are haven on using Chrysal concetrative 1000 mg (C4) for five or four days.